2016
DOI: 10.5664/jcsm.6264
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Novel Zolpidem Nasal Spray for Rapid Management of Insomnia: First Trial in Humans

Abstract: Study Objectives: The present single-dose, parallel-group, randomized, double-blind, placebo-controlled study is to evaluate the pharmacokinetics, tolerability and safety of zolpidem tartrate nasal spray (ZNS) as compared to placebo in healthy subjects. Methods: Thirty-six healthy subjects participated in this study, with 19 male and 17 female subjects in 3 cohorts (12 subjects per cohort), who were randomly assigned to receive either an intranasal dose of ZNS 1.75 mg, 3.5 mg, 5.0 mg (n = 10 per dose), or an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Forty study subjects were to participate in this study in order to meet the requirements of nominal significance level of 50 %, 2x2 crossover design, 80-125% equivalence range, 28% maximum CVintra for pharmacokinetic parameters, population ratio between 95-105% for treatment average plus an additional number of 8 volunteers to compensate possible losses due to dropout/exclusions. The planned number of subjects for the study is consistent with studies reported buy some authors [29][30][31] and higher than the number estimated by other [10,32]. The study was completed with 38 subjects, an amount higher than the 32 estimated volunteers in case of loss of the 8 subjects considered in the sample size determination, fact which contributed to maintain the obtained test power for pharmacokinetic parameters near 100%.…”
Section: Discussionsupporting
confidence: 80%
“…Forty study subjects were to participate in this study in order to meet the requirements of nominal significance level of 50 %, 2x2 crossover design, 80-125% equivalence range, 28% maximum CVintra for pharmacokinetic parameters, population ratio between 95-105% for treatment average plus an additional number of 8 volunteers to compensate possible losses due to dropout/exclusions. The planned number of subjects for the study is consistent with studies reported buy some authors [29][30][31] and higher than the number estimated by other [10,32]. The study was completed with 38 subjects, an amount higher than the 32 estimated volunteers in case of loss of the 8 subjects considered in the sample size determination, fact which contributed to maintain the obtained test power for pharmacokinetic parameters near 100%.…”
Section: Discussionsupporting
confidence: 80%
“…bioavailability, LC/MS/MS, pharmacokinetics, tandem mass spectrometry 1 | INTRODUCTION Zolpidem, a benzodiazepine receptor agonist, is a hypnosedative imidazopyridine that has a strong sedative action with minor anxiolytic, muscle relaxant or anticonvulsant properties. Zolpidem decreases the time to sleep onset and increases duration of sleep with effects on sleep stages (Greenblatt & Roth, 2012;Hoehns & Perry, 1993;Holm & Goa, 2000;Langtry & Benfield, 1990;Li et al, 2016;Salva & Costa, 1995;Swainston Harrison & Keating, 2005). It is administered as an oral standard immediate release tablet (5 and 10 mg), oral controlled release tablet (6.25 and 12.5 mg) or sublingual tablet (5 and 10 mg) for difficulty with sleep onset.…”
Section: Introductionmentioning
confidence: 99%
“…It is administered as an oral standard immediate release tablet (5 and 10 mg), oral controlled release tablet (6.25 and 12.5 mg) or sublingual tablet (5 and 10 mg) for difficulty with sleep onset. The sublingual tablet (1.75 mg women; 3.5 mg for men) is indicated for middle-of-the-night wakefulness, oral spray (5 mg) for difficulty with sleep initiation and nasal spray (1.75 mg, 3.5 mg, 5.0 mg) for sleep initiation difficulty and middle-ofthe-night awakening (Greenblatt & Roth, 2012;Hoehns & Perry, 1993;Holm & Goa, 2000;Langtry & Benfield, 1990;Li et al, 2016;Neubauer, 2010;Pergolizzi, Taylor, Raffa, Nalamachu, & Chopra, 2014;Salva & Costa, 1995;Swainston Harrison & Keating, 2005). The pharmacokinetics of zolpidem by sublingual administration is influenced by food intake and gender (Greenblatt et al, 2013;Greenblatt et al, 2014;Li et al, 2016;Pergolizzi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%